New insight into the organization of myelin water using deuterium NMR. Issue 2 (21st January 2020) - Eliav, Uzi; Wehrli, Felix W.; Navon, Gil
Abstract : Purpose: Myelin water is commonly characterized by its short proton T2 relaxation time, suggesting strong association with the polar head groups of the bilayer constituents. Deuterium NMR of water in ordered structures exhibits splittings as a result of quadrupolar interactions that are observable using the double‐quantum filter. The purpose of the current study was to identify and characterize the water populations. Methods: The 2 H double‐quantum‐filtered spectroscopic experiments were conducted at 62 MHz (9.4 T) on a sample of reconstituted myelin from ovine spinal cord after exchange of native water with D2 O. Results: Signals passing the double‐quantum filter were attributed to 2 water pools: 1 consisting of a doublet of 650‐Hz splitting, and a second unsplit signal. Similar signals were observed in the sciatic and optic nerves and in the spinal cord. Further, data suggest that diffusion of water molecules in these 2 pools (Dapp ≤ 5 × 10 −7 cm 2 /s) is either hindered or restricted. An estimate of exchange lifetime of 10‐15 ms between water pertaining to the single peak and that of the split peaks suggests exchange occurs in a slow‐intermediate rate regime. Further distinction between the 2 pools was obtained from T1 measurements. Deuterons belonging to the doublet resonance were found to have short T1, estimated to be on the order of 10‐20 ms, whereas those corresponding to the single peak were close to that of bulk D2 O. Conclusion: The results suggest that myelin extract water consists of 2 hindered populations with distinct degrees of anisotropic motion that can be studied by 2 H double‐quantum‐filtered NMR.